How to design effective educational videos for teaching evidence-based medicine to undergraduate learners – systematic review with complementing qualitative research to develop a practicable guide - Lukas Niekrenz; Cord Spreckelsen (Medical Education Online)
Background eLearning can be an effective tool to achieve learning objectives. It facilitates asynchronous distance learning, increasing flexibility for learners and instructors. In this context, the high educational value of videos provides an invaluable primary component for longitudinal digital curricula, especially for maintaining knowledge on otherwise rarely taught subjects. Although literature concerning eLearning evaluation exists, research comprehensively describing how to design effective educational videos is lacking. In particular, studies on the requirements and design goals of educational videos need to be complemented by qualitative research using grounded theory methodology.Methods Due to the paucity of randomized controlled trials in this area, there is an urgent need to generate recommendations based on a broader fundament than a literature search alone. Thus, the authors have employed grounded theory as a guiding framework, augmented by Mayring’s qualitative content analysis and commonly used standards. An adaptive approach was conducted based on a literature search and qualitative semi-structured interviews. Drawing on these results, the authors elaborated a guide for creating effective educational videos.Results The authors identified 40 effective or presumedly effective factors fostering the success of video-based eLearning in teaching evidence-based medicine, providing a ready-to-use checklist. The information collected via the interviews supported and enriched much of the advice found in the literature.Discussion To the authors’ knowledge, this type of comprehensive guide for video-based eLearning needs has not previously been published. The interviews considerably contributed to the results. Due to the grounded theory-based approach, in particular, consensus was achieved without the presence of a formal expert panel. Although the guide was created with a focus on teaching evidence-based medicine, due to the general study selection process and research approach, the recommendations are applicable to a wide range of subjects in medical education where the teaching aim is to impart conceptual knowledge.